Historical Archaeology and Environment (Springer International Publishing, 2018)
This edited volume gathers contributions focused on understanding the environment through the lens of Historical Archaeology. Pressing issues such as climate change, global warming, the Anthropocene and loss of biodiversity have pushed scholars from different areas to examine issues related to the causes, processes, and consequences of these phenomena. While traditional barriers between natural and social sciences have been torn down, these issues have gradually occupied a central place in the field of anthropology. As archaeology involves the transdisciplinary study of cultural and natural evidence related to the past, it is in a privileged position to discuss the historical depth of some of the processes related to environment that are deeply affecting the world today. This volume brings together substantial and comprehensive contributions to the understanding of the environment in a historical perspective along three lines of inquiry: Theoretical and methodological approaches to the environment in Historical Archaeology Studies on environmental Historical Archaeology Historical Archaeology and the Anthropocene Historical Archaeology and Environment will be of interest to researchers in both social and environmental sciences, working in different disciplines and research areas, such as archaeology, history, geography, anthropology, climate change studies, environmental analysis and sustainable development studies.